Myths and Legends in Crime Fiction - Francová, Michaela (Univerzita Pardubice, 2024)
The thesis deals with the use of myths and legends in crime fiction. It predominantly focuses on the works of Arthur Conan Doyle, Agatha Christie, and Dan Brown, specifically The Hound of the Baskervilles, The Labours of Hercules, Angels & Demons, and The Da Vinci Code. Additionally, it mentions the works of Ben Aaronovitch and Tendai Huchu. The aim of this thesis is to analyse how the authors used various myths and legends in their works.
Mýty a Legendy v Detektivní Próze
Keywords: detektivní próza; mýty; legendy; Doyle, Arthur Conan; Christie, Agatha; Brown, Dan; Sherlock Holmes; Pes Baskervillský; Hercule Poirot; Herkules; Šifra Mistra Leonarda; T. L. Huchu; crime fiction; myths; legends; Sherlock Holmes; Hound of the Baskervilles; Hercule Poirot; Hercules; Da Vinci Code